Local Experience in using Hormonal Therapies according to the UKISS Studies in the Treatment of Infantile Spasms in Hong Kong - Yuen, Chi Lap; Mo, Chung Yin (Journal of Pediatric Epilepsy, 2018)
Infantile spasms constitute severe epileptic encephalopathy in infancy with characteristic seizure semiology and electroencephalographic patterns. Besides the spasms, the most detrimental effect is the impact on future developmental outcomes. Different treatment methods are used, but hormonal therapy is the most well-accepted method for treating infantile spasms in nontuberous sclerosis cases. After the launch of the original United Kingdom Infantile Spasms Study (UKISS) and the two follow-up articles, the regimens of hormonal therapy became more structured and the expected treatment outcomes were studied better. We would like to share our local experience using this protocol to treat patients with infantile spasms in Hong Kong with a case series of four patients.
Keywords: infantile spasm; UKISS; treatment; prednisolone; ACTH